Cell-Mediated Immunity in Elite Controllers Naturally Controlling HIV Viral Load - Genovese, Luca; Nebuloni, Manuela; Alfano, Massimo (Frontiers in Immunology, 2013)
The natural course of HIV infection is characterized by high viral load, depletion of immune cells and immunodeficiency, ultimately leading to acquired immunodeficiency syndrome (AIDS) phase and the occurrence of opportunistic infections and diseases. Since the discovery of HIV in the early 80’s a naturally selected population of infected individuals has been emerged in the last years, characterized by being infected for many years, with viremia constantly below detectable level and poor depletion of immune cells. These individuals are classified as “elite controllers or suppressors” and do not develop disease in the absence of anti-retroviral therapy. Unveiling host factors and immune responses responsible for the elite status will likely provide clues for the design of therapeutic vaccines and functional cures. Scope of this review was to examine and discuss differences of the cell-mediated immune responses between HIV+ individuals with disease progression and elite controllers.